62.5k views
2 votes
6)What steps transform the graph of y = y? toy=-2(x + 1)2 + 3?

6)What steps transform the graph of y = y? toy=-2(x + 1)2 + 3?-example-1
User Vinalti
by
4.8k points

1 Answer

0 votes

We will have the following:

*If we graph the problem we will obtain:

So, the steps to transform the first graph into the second one are:

1). We multiply the move the graph 1 unit to the left:


x^2\to(x+1)^2

2). We reduce the opening of the graph by a factor of 2:


(x+1)^2\to2(x+1)^2

3). We invert the direction of the opening of the parabola:


2(x+1)^2\rightarrow-2(x+1)^2

4). We move the graph 3 units up:


-2(x+1)^2\rightarrow-2(x+1)^2+3

6)What steps transform the graph of y = y? toy=-2(x + 1)2 + 3?-example-1
User Chener
by
4.6k points